Community empowerment through a social capital approach in the development of tourism destination in Wawoangi Village - Hanifa, Lia; Azaluddin, Azaluddin; Arjuwita, Arjuwita; Karlina, Ayu Rezky; Riskawat, Riskawat (Community Empowerment, 2021)
This community service is carried out in Wawoangi Village, Sampolawa District, South Buton Regency in developing a tourist village. This community service program concludes that the role of social capital can be used for the community in the form of local knowledge, which can then be used as a means of mentoring, coaching, managing tourism and directing tourism object development to the village government and village communities. By managing tourism objects in Wawoangi Village, it will encourage the people's economy, especially by promoting all economic sectors in the village, be it handicrafts, agriculture, and culture.